Simulating the Effects of Some Simple Coordinated versus Uncoordinated Policy Rules. (IMF Working Papers; Working Paper ;, 1989)
Effects of different policy rules are simulated: uncoordinated targeting of the money supply or nominal income, use of monetary policy to achieve coordinated targets for nominal or real exchange rates, and the use of monetary and fiscal policies to hit targets for internal and external balance. The following conclusions emerge: rules which performed best for some shocks performed poorly for others; monetary policy was ineffective in limiting movements in real exchange rates; unconstrained use of fiscal policy was quite powerful in influencing real variables; and dynamic instability was a potentially serious problem. Robustness to different specifications and to constraints on instruments remains to be examined.